A arte como culto: o conceito de mana na apreciação da obra de arte - Paz, Daniel Juracy Mellado (2011)
ABSTRACT: This paper try to explain the actual relationship between man and the work of art from the now classic concept of aura of Walter Benjamin, and contrasting it to mana, used in the Sociology of Religion. The idea of mana, recurring phenomenon in many societies, allows reinterpret into a coherent whole the various phenomena of the contemporary world of the arts, such as the authenticity of the objects in serial production, the diffusion of works and general search by contact with the original, and overall, the affection for the objects.